2015
DOI: 10.1007/s12194-015-0326-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the saturation pulse duration on chemical exchange saturation transfer in amide proton transfer MR imaging: a phantom study

Abstract: Amide proton transfer (APT) contrast imaging is based on the chemical exchange saturation transfer (CEST) of protons between the amide groups and bulk water. Here, we demonstrate the effect of the saturation pulse duration on CEST in APT imaging with use of a clinical MR scanner. Four samples were prepared from chicken egg white diluted with H2O. Experiments were performed on a 3T clinical MR scanner with use of a body coil for two-channel parallel radiofrequency transmission. APT images were acquired at six f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 16 publications
1
18
0
Order By: Relevance
“…The RF saturation pulse is typically applied in the clinic at a low saturation power of 0.5–6 μT to improve the selectivity of saturating only the MR signal of the intended proton of a specific agent or biomolecule, hopefully without also saturating the MR signals of other protons, including water protons. In addition, the RF saturation is typically applied for a long duration of ∼1–5 seconds to allow saturation to reach steady state . During this saturation period, the exchange of protons between water and the agent or biomolecule can occur at a chemical exchange rate of ∼30–1000 Hz, thereby resulting in ∼30–5000 saturated protons transferred to water from each agent or biomolecule (ignoring the effects of T 1 relaxation).…”
Section: The Case For Cest Mri As a Molecular Imaging Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…The RF saturation pulse is typically applied in the clinic at a low saturation power of 0.5–6 μT to improve the selectivity of saturating only the MR signal of the intended proton of a specific agent or biomolecule, hopefully without also saturating the MR signals of other protons, including water protons. In addition, the RF saturation is typically applied for a long duration of ∼1–5 seconds to allow saturation to reach steady state . During this saturation period, the exchange of protons between water and the agent or biomolecule can occur at a chemical exchange rate of ∼30–1000 Hz, thereby resulting in ∼30–5000 saturated protons transferred to water from each agent or biomolecule (ignoring the effects of T 1 relaxation).…”
Section: The Case For Cest Mri As a Molecular Imaging Techniquementioning
confidence: 99%
“…In addition, the RF saturation is typically applied for a long duration of 1-5 seconds to allow saturation to reach steady state. 3,4 During this saturation period, the exchange of protons between water and the agent or biomolecule can occur at a chemical exchange rate of 30-1000 Hz, thereby resulting in 30-5000 saturated protons transferred to water from each agent or biomolecule (ignoring the effects of T 1 relaxation). With sufficient saturation and chemical exchange rate, as little as 2 mM of exchangeable protons on an exogenous agent or endogenous biomolecule can generate a 2% decrease in water signal, which can be quantitatively detected with standard MR acquisition methods (this evaluation is based on an estimate of 72% water composition in tissues; an exchange rate of 1600 Hz; saturation for 1 sec; 55.5 M concentration of H 2 O molecules in pure water; and two protons per H 2 O molecule).…”
Section: The Case For Cest Mri As a Molecular Imaging Techniquementioning
confidence: 99%
“…The choice of values for saturation time and irradiation power were based on the results of a study performed at 3 T to investigate the APT-CEST contrast. 22 In addition to the saturated images (S sat ), a reference image (S 0 ) without RF irradiation (B1 = 0 μT) was also acquired.…”
Section: Apt-cest Mrimentioning
confidence: 99%
“…In addition to the pulse shape, pulsed saturation brings additional factors to take into account for CEST contrast optimization: individual pulse length, inter-pulse gap, number of pulses, etc. For example, it has been reported that the inter-pulse gap may be utilized to improve the specificity of CEST agents [28, 29]. However in practice, the optimization of the saturation RF pattern is often performed experimentally, not only due to the high number of factors but also because the exchange rate in vivo cannot be exactly known [23, 30].…”
Section: Reviewmentioning
confidence: 99%